2023
DOI: 10.1039/d2mh01314b
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency organic solar cells processed from a real green solvent

Abstract: The fabrication of organic solar cells (OSCs) depends heavily on highly toxic chlorinated solvents, which are incompatible with industrial manufacturing. The reported alternative solvents such as non-halogenated aromatic hydrocarbons and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…[25,26] As shown in Figure 1 (red region), typically, these solvents, particularly non-halogen solvents, cannot afford PCEs as high as CF. [27] Most of the time, the eco-friendlier hydrocarbon solvents lead to PCEs significantly lower than CF, because the physical chemistry among donor-acceptor-solvent, for example, their phase diagram and the drying kinetics of the solution, are essentially different from fast-drying solvents such as CF. [28] Therefore, the conventional way of fabricating the active layer by blend-casting the co-dissolved donor and acceptor solution in one step, may not be able to achieve similar morphology when high boiling point solvents are used.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] As shown in Figure 1 (red region), typically, these solvents, particularly non-halogen solvents, cannot afford PCEs as high as CF. [27] Most of the time, the eco-friendlier hydrocarbon solvents lead to PCEs significantly lower than CF, because the physical chemistry among donor-acceptor-solvent, for example, their phase diagram and the drying kinetics of the solution, are essentially different from fast-drying solvents such as CF. [28] Therefore, the conventional way of fabricating the active layer by blend-casting the co-dissolved donor and acceptor solution in one step, may not be able to achieve similar morphology when high boiling point solvents are used.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of organic photovoltaics (OPVs) and organic fieldeffect transistors (OFETs), nonhalogenated solvents, such as 2methyltetrahydrofuran (2-mTHF), p-xylene, and 2-methylanisole (o-MA), have been employed in the deposition of active thin-films based on polymer semiconductors. [26][27][28][29] However, research on the ecofriendly solvent-processed polymer light-emitting diodes (PLEDs) has been rarely reported due to the limited solubility of LCPs resulted by rigid aromatic backbone and complex intermolecular interactions, [30] especially for the blue PLEDs, [31] where achieving high-efficient and stable electroluminescence (EL) remain huge challenges. [32][33][34] On the other hand, although the classification and ranking of green solvents varies slightly from organization to organization, they all make qualitative assessment according to the criteria: low health hazard, high safety, and small environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cao et al reported a B→N based conjugated polymer called PBNT-TzTz as a donor, which can be dissolved in the food-grade solvent anisole to make OSCs (Figure 5). [48] The good solubility of this B→N conjugated polymer is due to the large dipole moment originating from B→N units, resulting in Reproduced with permission. [44] Copyright 2021, Springer Nature Publishing Group.…”
Section: Huang Et Al Introduced a New Non-fullerene Acceptor Dty6mentioning
confidence: 99%
“…b)The chemical structures of the donor polymer PBNT-TzTz, its origination of dipole and solubility in anisole. Reproduced with permission [48]. Copyright 2023, The Royal Society of Chemistry.…”
mentioning
confidence: 99%